PERAN PERHIMPUNAN ALKHAIRAAT DALAM MEMPERKUAT MAZHAB SYAFI’I DI KOTA PALU - mohammad (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2021)
Perhimpunan Alkhairaat is one of the largest religious organizations in Eastern Indonesia, this institution is consistent with education and da'wah as well as social activities. In its guidance to Muslims, much emphasis is placed on the practice of the Shafi'i School, and this is the will of the founder of this institution, Sayyid Idrus bin Salim Al Jufri. The research method in this article uses a qualitative approach, data collection techniques through observation, interviews and documentation, data analysis techniques used are data reduction, data presentation and data verification. The results of this study also show that the role of the Alkhairaat Association greatly contributes to the strengthening of the Syafi'i School in Palu City, through education in madrasas in this case the development of Islamic law. And in his own da'wah, Alkhairaat is consistent with fostering in the community through teachers who are also preachers with Alkhairaat Alumni backgrounds through ta'lim assemblies. In addition, the Alkhairaat Association also encountered obstacles in strengthening the Syafi'i School in Palu City, namely in the form of infrastructure and the increasingly widespread and large distribution of the Alkhairaat madrasa so that all preachers who were directly involved in the community could not cover it. It is recommended to all abnaulkhairaat to always pay attention to madrasas wherever they are. Because from this madrasa is the foundation in shaping Islamic character